Reluctant Role Models: Men Teachers and the Reproduction of Hegemonic Masculinity - Sargent, Paul (Qualitative Sociology Review, 2013)
In-depth interviews with men teachers and other key personnel in early childhood education (ECE) revealed that the men are attempting to perform a type of subordinate masculinity that could challenge traditional gender relations. However, their attempts are thwarted by the gender regime embedded in the occupational structure, particularly the demand that they perform as “male role models” for the boys in their classes. This means that they are prescribed to perform in stereotypical ways and to purposely model traditional masculinity to boys, thereby inculcating hegemonic norms of masculinity.